Parental involvement intervention: effect on students’ self-efficacy and math achievement among a Nigerian sample - Akindipe, Olutola Opeyemi (Frontiers in Psychology, 2025)
Although math underachievement remains a global educational challenge, empirical evidence indicates that parental involvement interventions have significantly improved students’ performance in the subject. The problem, however, seems to persist in Nigeria where there are reports of low parental involvement and no extant studies of parental involvement intervention in math. This study examined the impact of parental involvement intervention on students’ math achievement and self-efficacy. The sample consisted of 51 fifth grade students recruited from 2 private schools in the Lagos educational district III that chose to participate in the study. Comprising 17 boys and 34 girls with an average age of 10.89 years, students from one of the schools served as the intervention group while the second school was the control group. The intervention group underwent home structure, parental supervision, and school-home communication intervention while the control group did not. Collected data was analyzed using analysis of covariance (ANCOVA) and independent t-test analyses. Results showed that the intervention significantly improved students’ math achievement but not math self-efficacy. Educational implications of the results are discussed.